Predictors and Outcomes of Healthcare-Associated Infections Caused by Carbapenem-Nonsusceptible Enterobacterales: A Parallel Matched Case-Control Study - Hoo, Grace S. R.; Cai, Yiying; Quek, Yan Ching; Teo, Jocelyn Q.; Choudhury, Saugata; Koh, Tse Hsien; Lim, Tze Peng; Marimuthu, Kalisvar; Ng, Oon Tek; Kwa, Andrea L. (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives: The increasing incidence of carbapenem-nonsusceptible Enterobacterales as major pathogens in healthcare associated infections (HAIs) is of paramount concern. To implement effective prevention strategies against carbapenem-nonsusceptible Enterobacterales (CnSE) HAIs, it is crucial to identify modifiable factors associated with these infections. We identified risk factors for CnSE-HAIs, and compared clinical outcomes of CnSE-HAI and carbapenem-sensitive Enterobacterales (CSE)-HAI patients. Methods: We conducted a multi-centre parallel matched case-control study in two 1700-bedded Singapore acute-care hospitals from 2014–2016. Patients with CnSE-HAIs and CSE-HAIs were compared to a common control group without HAIs (1:1:3 ratio), matched by time-at-risk and patient ward. Carbapenem nonsusceptible was defined as non-susceptibility to either meropenem or imipenem. Presence of healthcare associated infections were defined by the criteria provided by the European Centre for Disease Prevention and Control. Outcomes of CnSE-HAI and CSE-HAI patients were compared using multivariable logistic and cox regression; the models were adjusted for infection and treatment characteristics. Results: Eighty CnSE-HAI and 80 CSE-HAI patients were matched to 240 patients without HAIs. All CRE-HAIs patients had prior antibiotic exposure, with 44 (55.0%) with prior carbapenem exposure. The most common CnSE-HAIs were intra-abdominal infections (28.8%) and pneumonia (23.8%). The most common CnSE species was Klebsiella spp. (63.8%). In the risk factor analysis, presence of drainage devices [adjusted odds ratio (aOR), 2.19; 95% CI, 1.29 – 3.70] and prior carbapenem exposure (aOR,17.09; 95% CI, 3.06 – 95.43) independently predicted CnSE-HAIs. In the crude outcomes analysis, CnSE-HAI patients had higher all-cause in-hospital mortality and longer time to discharge compared to CSE-HAI patients. After adjusting for differences in receipt of antibiotics with reported susceptibility to the Enterobacterales, there was no significant difference in all-cause in-hospital mortality between the two groups (aOR, 1.76; 95% CI, 0.86–3.58). Time to discharge remained significantly longer in patients with CnSE-HAI (adjusted hazard ratio, 0.71; 95% CI, 0.51 – 0.98) after adjusting for disease severity, receipt of antibiotics with reported susceptibility and receipt of appropriate source control. Conclusion: Appropriate management of deep-seated Enterobacterales infections and reducing exposure to carbapenems may reduce risk of CnSE-HAIs in Singapore. Efforts to improve antimicrobial therapy in CnSE-HAI patients may improve patient outcomes.